The sociology of Catholicism: A review of research and scholarship. Issue 4 (5th March 2021) - Conway, Brian
Abstract: This article seeks to review recent research and scholarship in the sociology of Catholicism, as well as focusing on areas needing greater attention. In taking stock of this literature, I identify institutional change, church‐society interactions, institutional resources and influence, and the church as international actor as four key topics that have engaged scholarship. I review existing research under each, as well as highlighting gaps and blind spots that invite further inquiry of this specific religious group.